The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/19440049.2014.972992
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aflatoxin metabolism and growth ofAspergillus flavusin liquid culture by a DNA methylation inhibitor

Abstract: Aflatoxins (AFs) are a group of highly oxygenated polyketidese-derived toxins mainly produced by Aspergillus flavus and A. parasiticus, whose biosynthesis mechanisms are extremely sophisticated. Methylation is known as the major form of epigenetic regulation, which is correlated with gene expression. As the DNA methylation inhibitor 5-azacytidine (5-AC) blocks AF production, we studied AFB1 metabolism and morphological changes of A. flavus by treatment with 5-AC in liquid culture. The results show that 5-AC ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Aspergillus flavus is a saprophytic soilborne fungus that contaminates food-stuffs and a broad range of important agricultural crops, including maize, peanut, and cottonseed, with the most carcinogenic metabolite, aflatoxins (AFs) (Amaike and Keller, 2011; Yang et al, 2015). This fungus is also one of the most opportunistic pathogen of human and animals causing aspergillosis diseases or liver cancer either through consumption of contaminated food or through invasive growth (Hedayati et al, 2007; Amaike and Keller, 2011; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus flavus is a saprophytic soilborne fungus that contaminates food-stuffs and a broad range of important agricultural crops, including maize, peanut, and cottonseed, with the most carcinogenic metabolite, aflatoxins (AFs) (Amaike and Keller, 2011; Yang et al, 2015). This fungus is also one of the most opportunistic pathogen of human and animals causing aspergillosis diseases or liver cancer either through consumption of contaminated food or through invasive growth (Hedayati et al, 2007; Amaike and Keller, 2011; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This fungus is also one of the most opportunistic pathogen of human and animals causing aspergillosis diseases or liver cancer either through consumption of contaminated food or through invasive growth (Hedayati et al, 2007; Amaike and Keller, 2011; Yang et al, 2015). Because of this, A. flavus causes food shortages, significant economic losses and health problems all over the world especially in warm and moist fields (Amaike and Keller, 2011; Bai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins (AFs), mainly produced by A. flavus and A. parasiticus , have been identified as a class of the most toxic and carcinogenic secondary metabolites of fungi. AF contamination of agricultural grains is not only a significant food safety concern but also an economic concern for the agricultural industry worldwide (Yu, 2012; Amaike et al, 2013; Yang et al, 2015). To develop effective and novel strategies against AF contamination, it is a necessity to investigate the molecular mechanisms by which AF biosynthesis is regulated in A. flavus .…”
Section: Introductionmentioning
confidence: 99%
“…AF biosynthesis is extremely sophisticated (Klich, 2007;Yang et al, 2015). Generally, the AF biosynthesis genes of the most known AF producers, A. flavus and A. parasiticus, are highly homologous and the order of 25 genes within the AF gene clusters in the two organisms has been shown to be identical (Jiujiang et al, 1995).…”
Section: Aflatoxin Biosynthesis and Regulationmentioning
confidence: 99%
“…The mechanism of AF biosynthesis has been extensively studied, and recent investigations have shown that about 30 clustered genes and more than 23 steps of enzymatic reactions are involved in the AF biosynthetic pathway (Georgianna and Payne, 2009;Yu, 2012;Yang et al, 2015). AF biosynthesis is extremely sophisticated (Klich, 2007;Yang et al, 2015).…”
Section: Aflatoxin Biosynthesis and Regulationmentioning
confidence: 99%